Diseases of Cannabis sativa Caused by Diverse Fusarium Species - Gwinn, Kimberly D.; Hansen, Zachariah; Kelly, Heather; Ownley, Bonnie H. (Frontiers in Agronomy, 2022)
The potential of species of Fusarium to cause significant economic losses in Cannabis sativa due to plant diseases and mycotoxin residues is the subject of this review. Sixteen species of Fusarium, reported as associated with cannabis production, are classified in six species complexes: Fusarium oxysporum, F. solani, F. incarnatum-equiseti, F. sambucinum, F. tricinctum, and F. fujikuroi. Taxonomy in this genus is the subject of debate, and removal of species in the F. solani Species Complex to the genus, Neocosmospora, has been proposed. Many species associated with C. sativa are also opportunistic pathogens of humans and animals. Species of Fusarium produce a myriad of mycotoxins, including at least three (deoxynivalenol, zearalenone, and fumonisin B) deemed the most important mycotoxins in human and animal foods. These chemicals vary from the very simple chemicals (moniliformin and butanolide) to the structurally complex depsipeptides (beauvericin and enniatin B) and trichothecenes (deoxynivalenol and its acetylated derivatives, diacetoxyscirpenol, and T-2-toxin). The robust strategies for disease management (e.g., exclusion of the pathogen, control of environment, and host resistance) are in development for this new crop and have primarily relied on management systems for other crops. Biopesticides have been labeled for use on C. sativa; however, few efficacy trials have been performed. Host resistance to these pathogens and transmission are also understudied. The new markets for C. sativa and its derivative products require knowledge for control of these important fungal diseases to provide safe products for human consumption.